PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DINAS PERTANIAN, PANGAN DAN PERIKANAN KABUPATEN TASIKMALAYA - Lindayani, Cincin (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2021)
Based on the author's initial observations, data was obtained that there was a decrease in production yields of various types of agricultural commodities in Tasikmalaya Regency, which showed a lack of employee performance at the Tasikmalaya Regency Agriculture, Food and Fisheries Service in several indicators that were thought to have not maximized the leadership function. This study aims to analyze the magnitude of the influence of leadership on employee performance. The research method used is explanatory research with a quantitative approach, the data obtained through the distribution of questionnaires to 72 respondents, and data analysis used path analysis, because the authors wanted to know the influence of each leadership dimension on employee performance. The results of data processing with the SPSS version 22 program are known that leadership has a strong influence on employee performance with a contribution of 64.4%, and the remaining 35.6% is influenced by other variables not examined. Partially, the leadership dimension that has the greatest influence on employee performance is the inspirational dimension (58.15%), the second largest influence of the leadership dimension on employee performance is the visionary dimension (18.63%).